PERHITUNGAN STRUKTUR GEDUNG RENCANA RUMAH SUSUN DI KOTA SAMARINDA - NOVIANTO, RIZAL (KURVA S JURNAL MAHASISWA, 2016)
Increasing number of development in various areas, especially areas Samarinda in facilities and infrastructure to support the daily needs in the form of buildings, bridges and others. Flats is a building that is widely used as a human dwelling and also to indulge in daily activities such as household. Therefore planned a plan of building flats in the city of Samarinda in East Kalimantan.Study of Reinforced Concrete Structures in the Building 10 Floor Plan of flats in the city of Samarinda in East Kalimantan analysis based on existing data for the planned two methods of matrix and Sap 2000 with the aim to find out what work load in these structures.From the results of the analysis results obtained load acting on a portal that is dead loads, live loads and wind loads. Based on the results of comparative analysis of the structure with the two methods taken the greatest moment so that the value obtained, the beam Mu = 54.554 tons / m, column Pu = 27.150 tons / m, sloof Mu = 23.516 ton / m.From the planning and calculations that have been done shows the dimensions and reinforcement of structural elements (beams, columns, plates and foundations) as well as the plans of the structure for planning the building of flats in the city of Samarinda.